2015
DOI: 10.5505/tjoncol.2015.1204
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative theraphy methods used in the management of chemotherapy induced nausea and vomiting

Abstract: Patients with cancer apply for complementary medicine methods for the ineliminable symptoms such as nauseavomiting. Complementary and alternative medicine methods administered by patients in whom chemotherapy induced nausea vomiting developed were explained in this study. The primary complementary and alternative medicine methods that cancer patients frequently use were herbal products, relaxation, hypnosis, acupuncture, acupressure, yoga, meditation, massage, music, reflexology, cryotherapy, and aromatherapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Nausea-vomiting induced by chemotherapy is related to a significant reduction in quality of life, which is perceived by patients as a negative effect of the therapy [35,36]. Nausea-vomiting induced by chemotherapy, the most commonly reported side effect, is observed in 38-80% of patients receiving cancer treatment and its severity varies from patient to patient [37]. Lack of appetite, on the other hand, refers to weight loss as a result of less intake of nutrients than an individual's metabolic needs.…”
Section: Side Effects Of Chemotherapy and Nursing Carementioning
confidence: 99%
“…Nausea-vomiting induced by chemotherapy is related to a significant reduction in quality of life, which is perceived by patients as a negative effect of the therapy [35,36]. Nausea-vomiting induced by chemotherapy, the most commonly reported side effect, is observed in 38-80% of patients receiving cancer treatment and its severity varies from patient to patient [37]. Lack of appetite, on the other hand, refers to weight loss as a result of less intake of nutrients than an individual's metabolic needs.…”
Section: Side Effects Of Chemotherapy and Nursing Carementioning
confidence: 99%
“…Resmî Gazete, 2014). Music, which is one of the non‐pharmacological methods, is one of the frequently applied methods to cancer patients (Arslan & Özdemir, 2015; Demiray, 2020; Korkan & Uyar, 2014) and is preferred (Çokmert et al, 2011; Özcan & Pınar, 2021; Yildirim & Gürkan, 2007) for symptom control.…”
Section: Introductionmentioning
confidence: 99%
“…Music, by affecting the mood of the people and sedating, distracts the attention, enables patients to suspend themselves from their pain and is beneficial in reducing pain‐intensifying emotions such as anxiety and fear (Arslan & Özer, 2007). Using music in cancer treatment process provides relaxation in patients and reduces symptoms such as stress, pain and anxiety caused by cancer and its treatments (Arslan & Özdemir, 2015). In the carried out studies, it has been shown that music practices have a positive effect on reducing pain (Binns‐Turner et al, 2008; Bradt et al, 2016; Danhauer et al, 2010; Gutgsell et al, 2013; Krishnaswamy & Nair, 2016; Li et al, 2012; Moradian et al, 2015) and anxiety levels (Binns‐Turner et al, 2008; Bradt et al, 2016; Danhauer et al, 2010; Krishnaswamy & Nair, 2016; Palmer et al, 2015; Zhou et al, 2015) in cancer patients (Fernando et al, 2019; Jasemi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the CAM methods that cancer patients frequently resort to in symptom control regarding nausea-vomiting, it is seen that these methods mainly include plant-based products, as well as aromatherapy, hypnosis, reflexology, acupressure, music, meditation, massage, yoga, acupuncture, and relaxation 14,15 . Today, chemotherapy is applied frequently at outpatient chemotherapy units, and patients face problems caused by chemotherapy when they get home.…”
Section: Introductionmentioning
confidence: 99%
“…Today, chemotherapy is applied frequently at outpatient chemotherapy units, and patients face problems caused by chemotherapy when they get home. In some cases, the chemotherapy unit's education falls insufficient in patients' coping with problems they experience at home 14,15 . For this reason, this study was planned by considering that investigation of the nonpharmacological method usage statuses of individuals receiving chemotherapy as outpatients in management of chemotherapy-related nauseavomiting will shed light on clinical practices and be exemplary for studies to be conducted in this field.…”
Section: Introductionmentioning
confidence: 99%